Scenari- Based Planning and Its Application in Sustainable Urban Regeneration (Case Study: Deteriorated Urban Context of Dargahan, Qeshm Island) - Ali Toobchi Sani; Mohammad Masoud; Asadollah Rabbani; Golnaz Sarami Foroshani (توسعه پایدار شهری)
Today's world is complicated and unreliable, and tomorrow's world is expected to be much more complex and unreliable. In such a situation, understanding the nature of cities is more complicated than is thought. The scope and depth of this challenge increase every day due to a wonderful mixture of ambiguity, complexity, uncertainty, and tsunamis of change surrounding the city and the current world. Generally, these changes have emerged in a short period of time and create a deep gap between the time required and the available time to adapt to these changes. In this research, with the help of scenario planning, an attempt has been made to face complex and changing conditions in the regeneration of the deteriorated context of Dargahan city which is in a way the regional trade center of the south of the country. By verifying the key factors and driving forces of the changes, with the transition from the prediction of the definite future to the drawing of alternative futures, the preferred scenario was determined. Based on that, the framework of regeneration and planning in the run-down context of Dargahan is explained. According to the optimal scenario resulting from the process, an optimal cultural-economic regeneration approach has been proposed for this context. Avoiding superficiality and ignoring the hidden socio-economic layers, while dealing with different dimensions of instability, reverses the cycle of decline and providing a new opportunity to develop and realize a common vision. Therefore, this research is practical in terms of essence, and in terms of method, it is a case study based on scenario-oriented planning and Cross-Impact Balance analysis (CIB) and using Scenario Wizard software. Documentary studies, field observations, exploratory interviews, and expert panels have also been used to collect data.